Endangered man and the reply of the Christian from the viewpoint of theology* - Coetzee, P. J. (Koers, 1979)
In the story of creation (Gen. 1:26-2:3 and Gen. 2:4-25) the full emphasis falls firstly on the fact that man is the high point of Creation and then emphasis shifts to the fact that man represents the point of departure for history. On the one hand man is related to the lower orders of reality as he has been created out of the “dust of the earth” . On the other hand he should be distinguished on the grounds of principle as it emerges that he was created as the result of a deliberate mutual deliberation of the Trinity; God initiated his life by giving him breath; and it is of the greatest import that man was created in the image of God. As would appear from Genesis 5:3 where these same words are used in a reversed order, this double expression indicates that man was a likeness of God. This image has determined his humanity and has meant that he has a claim on communion with God through faith.